Effects of shelling maize cobs on the oviposition and development Sitophilus zeamais Motschulsky - Kossou, D.K.; Bosque Pérez, N.A.; Mareck, J.H. (Elsevier, 1992)
Oviposition and development of Sitophilus zeamais Motschulsky were studied on shelled maize kernels and unshelled cobs of the variety “Blanc Deux Precoce” from the Republic of Benin. On unshelled cobs adult weevils must feed and oviposit mostly on the kernel's crown, the only part of the kernel fully exposed to the external environment. The resistance of unshelled kernels to the maize weevil, relative to shelled kernels, is shown to depend on three factors: (1) reduced oviposition, as a result of non-preference for oviposition on the kernel's crown; (2) an increase in weevil median development period (MDP) due to the less suitable endosperm diet of first instar larvae which hatch from eggs laid on or near the crown; and (3) an additional increase in MDP due to difficulty in finding a site on the kernel where the F1 generation adult can emerge. These resistance factors, which contribute to lower levels of weevil infestation in traditional on-the-cob maize storage, have not been thoroughly investigated before. Other kernel and cob characteristics which appear to contribute to resistance are also discussed.